Apakah Efek Januari akan menyongsong Sang Naga Kayu? - Budiarso, Novi; Pontoh, Winston (Manajemen Bisnis dan Keuangan Korporat, 2024)
The January effect is an anomaly of the weak-form efficient market hypothesis. The January effect is one of the common issues that spreading in the capital market in early 2024, especially ahead of The Year of the Wood Dragon. In general, the Year of the Wood Dragon is believed to have hopes and optimism among some investors amidst developing global economic issues. The sample used for this study is the market index and returns in Indonesia throughout 2023 and the estimation results for January 2024. The findings show that the market index for January 2024 tends to be higher than December 2023 and has significant differences. However, the return of January 2024 tends to be smaller and is not significantly different from the return of December 2023. In the context of the efficient market hypothesis, although the market index movement pattern tends to be inconsistent with a weak form but the market return does not allow for anomalies in this form. This condition implies that the January effect will not occur before The Year of Wood Dragon of 2024.